IMPLEMENTASI PROGRAM ASUHAN KEPERAWATAN BERBASIS KOMUNITAS SEBAGAI MODEL PEMBELAJARAN KEPERAWATAN GERONTIK DI BANTUL - Nopryan Ekadinata; Laili Aisyah Rahmadani; Maylika Nissa Alvian; Ghina Fadhilah (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2024)
Geriatric syndromes are major issues for the elderly, hence calling for research that detects the syndromes’ presence and what interventions are suitable for addressing elderly needs. The research descriptively reports field findings concerning health and nursing problems of the elderly in Kalirandu, Bantul. It engages with field trip assignments from the gerontic nursing course or block, Universitas Muhammadiyah Yogyakarta. The assignments aim to elevate student learning experiences by providing them with hands-on experiences related to geriatric syndromes in the community. The fifth-semester students in the school of nursing carried out 160 visits to 160 elderlies in the research area. Respondents or treated elderlies were determined using the consecutive sampling mechanism. The treatments comprised hypertension screening, body mass index, and distributing research forms for geriatric syndromes. Sleep disorders and falling risks were the two most common nursing problems identified. Most interventions given to the elderly included education regarding geriatric syndromes, diets, zikr therapy, and relaxation therapy. Learning programs were conducted through field trips, proven to contribute positively to enhancing student understanding of how to give nursing care plans to the elderly. The synergy between the campus and the community must be optimized to escalate the health quality of the elderly.